(untitled) (Моделювання, керування та інформаційні технології, 2025)
We employ the method of a priori inequalities in negative norms to prove the existence of a pointwise optimal control for the regularized problem corresponding to a time-nonlocal pseudoparabolic integro-differential equation with a Volterra-type integral term. Certain differential properties of the cost functional are investigated, and a numerical example illustrating the computation of the optimal control is presented.